2020
DOI: 10.1021/acs.jafc.0c03922
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Polypeptides on Polylactic Acid Films and Their Application to Fresh Beef Preservation

Abstract: To enhance the advantage of a long-term stability and low-toxicity active packaging system, two biodegradable covalent immobilized antibacterial packaging films were developed and applied to fresh beef preservation in this study. A polylactic acid (PLA) film was prepared by the extrusion-casting method. The surface of the PLA film was modified with plasma treatment to generate carboxylic acid groups, and then antibacterial agent nisin or ε-poly lysine (ε-PL) was covalently attached to the modified film surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…The results showed that covalent immobilized antibacterial packaging films had positive impacts on the shelf-life and quality of fresh beef. The total viable count of the control sample and ε-PL-g-PLA film/nisin-g-PLA film exceeded 7 log CFU/g on the 11 days and 15 days of cold storage, respectively [52].…”
Section: Polysaccharidesmentioning
confidence: 87%
See 1 more Smart Citation
“…The results showed that covalent immobilized antibacterial packaging films had positive impacts on the shelf-life and quality of fresh beef. The total viable count of the control sample and ε-PL-g-PLA film/nisin-g-PLA film exceeded 7 log CFU/g on the 11 days and 15 days of cold storage, respectively [52].…”
Section: Polysaccharidesmentioning
confidence: 87%
“…Among the bio-derived materials, PLA (discussed below in Section 2.2) has received a special attention as one of the most attractive short-use packaging materials due to its good transparency, compostability, high rigidity and modulus at room temperature, and lack of ecotoxicity [50,51]. Very briefly and in the objective of enhancing the long-period stability and reduced toxicity of active packaging systems, several strategies were proposed, among which two biodegradable covalent immobilized antibacterial packaging films for fresh beef preservation were investigated [52]. A PLA film was prepared by extrusion casting and the surface of the film was modified with a plasma treatment to generate carboxylic acid groups, then an antibacterial agent nisin or ε-poly-lysine (ε-PL) was covalently attached to the modified film surface.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…The chemical structures of the FGSA-based layer and PLA from the obtained bilayer films were characterized by FTIR, as shown in Figure 1 c. Typical absorption bands of PLA were recorded in the spectrum: C=O carbonyl stretching (1750 cm −1 ), C−H stretching of −CH 3 (1452 cm −1 and 1382 cm −1 ), C−O stretching (1181 cm −1 and 1081 cm −1 ), and −OH bending (1014 cm −1 ) [ 27 , 28 , 29 ]. The FTIR spectra of all FGSA-based layers showed similar characteristic bands: amide-I (C−O stretching), amide-II (N−H bending), and amide-III (C−N and N−H stretching) with the location of the peaks at approximately 1645 cm −1 , 1552 cm −1 , and 1240 cm −1 in order, as well as a broadband peak around 3287 cm −1 owing to the superposition of the hydroxyl group and the amino group [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surface hydrophobicity of films was determined through the water contact angle (WCA) parameter according to the method described by Huang et al [ 27 ]. A droplet of distilled water (3 μL) was carefully dropped on the film surface using a microsyringe, and then the contact angles and images were recorded immediately by a JC2000c video-based contact angle meter (Shanghai Zhongchen Digital Technic Apparatus co., Ltd., Shanghai, China)…”
Section: Methodsmentioning
confidence: 99%
“…Copolymerization with other monomers is another approach that has been used to improve the properties such as stiffness, permeability, crystallinity, and thermal stability [ 8 , 27 , 28 , 29 ]. Covalent immobilization of polypeptides on PLA films can make it an active packaging [ 30 ]. Adding filler and plasticization was explored as an economically viable way to modify the properties of PLA resin.…”
Section: Introductionmentioning
confidence: 99%